Oppositional Identities and Employment for Ethnic Minorities. Evidence from England - Harminder Battu; Yves Zenou (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Where a community or group is socially excluded from a dominant group, some individuals of that group may identify with the dominant culture and others may reject that culture. The aim of this paper is to investigate this issue by empirically analyzing the potential trade-off for ethnic minorities between sticking to their own roots and labour market success. We find that the social environment of individuals and attachments to culture of origin has a strong association with identity choice. Our results also suggest that those non-whites who have preferences that accord with being "oppositional" do experience an employment penalty.
Keywords: J15; 330; Ethnic minorities; identity; social networks; white's norm